Heterosis Derived From Nonadditive Effects of the BnFLC Homologs Coordinates Early Flowering and High Yield in Rapeseed (Brassica napus L.) - Fang, Caochuang; Wang, Zhaoyang; Wang, Pengfei; Song, Yixian; Ahmad, Ali; Dong, Faming; Hong, Dengfeng; Yang, Guangsheng (Frontiers in Plant Science, 2022)
Abstract Early flowering facilitates crops to adapt multiple cropping systems or growing regions with short frost-free season; however, it usually brings an obvious yield loss. Here, we identified the three genes, BnFLC.A2, BnFLC.C2, and BnFLC.A3b, are the major determinants for the flowering time variation of two elite rapeseed (Brassica napus L.) accessions, i.e., 616A and R11.The early-flowering alleles (Bnflc.a2 and Bnflc.c2) and late-flowering allele (BnFLC.A3b) from R11 were introgressed into the recipient parent 616A through a marker-assisted backcross breeding strategy, giving rise to 8 homozygous near-isogenic lines (NILs) associated with these three loci and 19 NIL hybrids produced by mutual crossing of these NILs. Phenotypic investigations showed that NILs displayed significant variations in both flowering time (FT) and plant yield (PY). Notably, genetic analysis indicated that BnFLC.A2, BnFLC.C2 and BnFLC.A3b have additive effects of 1.446 g, 1.365 g and 1.361 g on PY respectively, while their dominant effects reached 3.504 g, 2.991 g and 3.284 g, respectively, indicating that the yield loss caused by early flowering can be successfully compensated by exploring the heterosis of FT genes in the hybrid NILs. Moreover, we further validated that the heterosis of FT genes in PY was also effective in non-NIL hybrids. Our results demonstrate that the exploration of the potential heterosis underlying the FT genes can coordinate early flowering (maturation) and high yield in rapeseed (Brassica napus L.), providing an effective strategy for early flowering breeding in crops.